Comparison of the Level of C-reactive Protein in Pre-eclampsia and Normal Pregnancy - Shaikh, Fozia; Khidri, Feriha Fatima; Laghari, Mubeena; Shaikh, Farhana; Daudpota, Sania Feroz (Journal of Liaquat University of Medical & Health Sciences, 2020)
OBJECTIVES: To measure the serum C-reactive protein levels in women with pre-eclampsia and compare its level in the normal pregnant women. METHODOLOGY: This comparative cross-sectional study was conducted in the biochemistry department, Liaquat University of medical and health sciences (LUMHS), Jamshoro from January to June 2017. A total of 80 subjects were recruited and grouped into n=40 women with normal pregnancy (control) and n=40 women with pre-eclampsia (cases) by non-probability consecutive sampling technique. The serum concentrations of C-reactive protein were determined by immunoturbidimetric assay. The variables were analyzed on SPSS software version 16 and p?0.05 was considered as significant. RESULTS: There was no significant difference in the age (p-value = 0.52) and gestational age (p-value = 0.09) between women with pre-eclampsia and normal pregnancy. Mean serum C-reactive protein concentration was significantly raised (p-value < 0.001) in women with pre-eclampsia (2.80±1.3 mg/dl) in comparison to normal pregnant women (0.63±0.39 mg/dl). CONCLUSION: The findings of this study indicated the increased C-reactive protein levels in women with preeclampsia as compare to normal pregnant women. The level of C-reactive protein can be utilized as inflammatory and biochemical marker in the pre-eclampsia. Furthermore, screening of pregnant women for C-reactive protein levels during early antenatal period in high risk obstetrical cases may be helpful in diagnosis of pre-eclampsia, which may reduce the feto-maternal morbidity and mortality.